Cancer Mortality by Ethnicity in Colombia Between 2011 and 2022: A Population-Based Study - Maria Camila Urrea Suescun; Isabel C. Garcés-Palacio; Amr S. Soliman (International Journal of Public Health)
ObjectivesTo examine cancer mortality rates in Colombia by ethnic groups (Indigenous, Rom, Raizal, Afro-Colombian, and Mestizo) and assess trends from 2011 to 2022.MethodsNational vital statistics from death certificates and the Colombian census data were used. Crude and direct age-standardized mortality rates were determined by ethnicity for the study period, by year, sex, and cancer type and Joinpoint analysis was conducted to examine trends.ResultsAge-standardized cancer mortality of Mestizos (60.1 per 100,000 population) was lower than in Rom and Raizales (557.3 and 77.7 per 100,000), and higher than for Afro-Colombians and Indigenous (37.2 and 20.0 per 100,000). Indigenous people in Colombia had greater proportions of individuals under 45 dying of cancer than Mestizos (18.7% vs. 9.7%, p-value = <0.01). Compared to the Mestizo population, Raizales and Afro-Colombians experienced disproportionately higher age-standardized mortality rates due to prostate cancer (26.6/100,000 and 8.6/100,000 vs. 8.1/100,000), and for Raizales and Rom breast cancer (14.0/100,000 and 103.2/100,000 vs. 9.1/100,000).ConclusionThe disparities in cancer mortality in ethnic minorities in Colombia call for investigating cancer etiology and access to care among the Rom and the Raizal populations.